Tax E-Filing System Acceptance Level on the Taxation Compliance: An Application of the UTAUT Approach - Natasya, Natasya; Tandililing, Elia Madatu; Angelus, Michael; Kevin, Kevin (Bina Nusantara University, 2019)
This research aimed to analyze the acceptance level of the tax e-filing system on the tax compliance of the individual taxpayer. UTAUT had underpinned this research that consisted of the aspects of Performance Expectancy (PE), Effort Expectancy (EE), Social Influence (SI), and Facilitating Condition (FC). These factors were expected to trigger the taxpayer attitude which will be impact on their behavioral intention. Using a qualitative research approach, an interview with 16 individual taxpayers with certain criteria was conducted. The interview questions were derived from the UTAUT aspects. Moreover, all interview scripts segmented into three distinct classifications; age, gender, and occupation. The interview data were analyzed using Nvivo 12. The result shows that tax e-filing system is effective to stimulate the commitment of the participant, not only to use the system regularly and to report their tax return but also to fulfill their tax obligation voluntarily. The e-filing system increases participant productivity because it offers cost reduction and time-saving. Furthermore, it is easy to understand and effortless to use. However, SI has less impact on the participant' decision to use tax e-filing system since it is mandatory in accordance with the tax regulation. Regarding the FC, it is sufficient to develop people interest in using the e-filing system. This result could be a beneficial source for the Directorate General of Taxes to evaluate the e-filing implementation and for Indonesia citizen to actively involved